A Comprehensive Survey of Pelagic Megafauna: Their Distribution, Densities, and Taxonomic Richness in the Tropical Southwest Indian Ocean - Laran, Sophie; Authier, Matthieu; Van Canneyt, Olivier; Dorémus, Ghislain; Watremez, Pierre; Ridoux, Vincent (Frontiers in Marine Science, 2017)
The distribution and density of pelagic megafauna (marine mammals, seabirds, elasmobranches and sea turtles) are important indicators of marine biodiversity, reflecting the condition of the underlying ecosystems. Taking advantage of their relative accessibility at the sea surface, a dedicated aerial survey was conducted in the tropical Southwest Indian Ocean to map their distribution, the taxonomic diversity and to estimate their densities for a reference standpoint on the area. This large survey across three ecological sub-regions revealed contrasting spatial distributions: maps of taxonomic richness of marine mammals and seabirds revealed different “hotspots” in the area. Densities were estimated for eight cetacean taxa with small and large Delphininae, or small Globicephalinae dominating, and for seven seabird taxa, with terns and noddies dominating. At the community level, the Southwest Indian Ocean megafauna was structured by the marine environment with strong differences between the Mozambique Channel and the Mascarene Islands, or between shelf and slope/oceanic habitats. Our results illustrate how multi-taxa aerial surveys are relevant and cost-effective monitoring tools for marine megafauna, allowing a community-wide approach.